The eyes test is influenced more by artistic inclination and less by sex - Guariglia, Paola; Piccardi, Laura; Giaimo, Flavio; Alaimo, Sofia; Miccichè, Giusy; Antonucci, Gabriella (Frontiers in Human Neuroscience, 2015)
The ‘Reading the Mind in the Eyes’ test was developed by Baron-Cohen and his co-workers. This test provides them the unique opportunity to evaluate social cognition assessing the ability to recognize the mental state of others using only the expressions around the eyes. In healthy populations, however, it has produced conflicting results, particularly regarding sex differences and number of items to use. In this study we performed two studies: The first one investigated the presence of gender effects and the sensitivity of test stimuli; the second one considered other individual factors (i.e. artistic attitude, social empathy and personality traits) that could influence the ability to understand emotions from gaze. Our results demonstrated a sex effect, which can be more or less attenuated by the nature of the stimuli. This could be as aforementioned the result of the following, empathy or artistic attitude in being proficient in understanding the mental states of others.